Maqasid al-Sharia in Court-Mediation Reform: A Study on Efficiency and Social Justice in Medical Disputes - Herliana, Herliana (De Jure: Jurnal Hukum dan Syari'ah, 2023)
Islam prioritises peace as a means of resolving disputes. Peace between parties can be achieved in various ways, one of which is mediation. Despite creating social justice, the effectiveness of mediation in resolving various complex civil cases is still questionable. This article aims to analyse the efficiency of resolving medical disputes through mediation based on the principles of Islamic law. This article is based on the results of normative juridical research with a statutory approach and a conceptual approach. The results of this study found that the implementation of facilitative mediation by the mediator in medical dispute resolution helps improve its efficiency. Furthermore, before mediating conflicts, judge-mediators need to take a more proactive position, improve their communication skills, and have sufficient knowledge of health law. A well-informed mediator is likely to provide social justice for doctors and patients. Keywords: mediation; medical disputes; social justice; court.